The relationship between front foot position and lower limb and lumbar kinetics during a drag flick in specialist hockey players - Wild, Catherine; Rosalie, Simon; Iyengar, Smitha; Ng, Leo; Sherry, D.; Loh, W.; Sjurseth, A. (Sports Medicine Australia, 2016)
Introduction: The penalty corner set play is one of the most important scoring tools in field hockey and the drag flick (DF) is used preferentially over hitting, due to the height restriction imposed on hits at goals. Recently, research has reported that players who DF have significant higher odds of hip (54%) and back injuries (56%) than non-drag flickers. Furthermore, there is anecdotal evidence to support that variation in the front foot placement (open or closed) during a DFmay result in changes to lower limb and lumbar spine biomechanics, potentially playing a role in the injury risk in DF. However, to date no study has investigated the effect of front foot position during a drag flick to support this hypothesis. The aim of this study was to examine the relationship between front foot position and lower limb and lumbar spine joint kinetics during a DF in specialist hockey players. Methods: Twenty-five males (n = 18) and female (n = 7) specialist DF hockey players (age = 23.0 ± 3.1 years; height = 1.81 ± 0.05 m; mass = 80.5 ± 11.4 kg) participated in this study. Participants performed up to five DF using their preferred front foot position, during which three- dimensional lower limb and lumbo-pelvic kinematics (250 Hz), and ground reaction forces (2000 Hz) were assessed. Front foot position was defined as the angle formed between the long axis of the foot and the anterior plane of motion (open position < 45◦; closed position > 45◦). Pearson correlations were used to assess the relationship (p < 0.05) between front foot position and lower limb and lumbo-pelvic joint reaction forces and external joint moments at the time of ball release. Results: In terms of foot angle at the time of ball release (31.4 ± 16.1◦), a correlation was displayed for medial shear (r = 0.73, p < 0.01) and compressive (r = −0.24, p = 0.02) forces at the ankle. Weak to moderate positive correlations were found at the knee for tensile forces (r = 0.46, p < 0.01) and adduction moments (r = 0.39, p < 0.01) and a positive correlation was displayed for anterior (r = 0.43, p < 0.01) and compressive (r = 0.33, p < 0.01) lumbo-pelvic forces at the time of ball release. Discussion: Results suggest that an increase in foot angle at ball release (closed front foot position) is associated with greater medial shear forces at the ankle as well as anterior lumbo-pelvic forces, which may play a role in the risk of injury in specialist DF.